'Mézclalo un poquito': plurilingual practices in multilingual educational milieus. Issue 1 (2nd January 2020) - Llompart, Júlia; Masats, Dolors; Moore, Emilee; Nussbaum, Luci
ABSTRACT: We analyse data collected at multilingual schools in Catalonia, taking a plurilingual and socio-cultural Conversation Analysis approach to the interactions studied. The analytical sections of the article show how plurilingual practices are resources for students' participation in classroom activities; we argue that language learning is a process that is reflected in how students' participation is achieved and modified in classroom interaction over time, and in the ways in which they mobilise interactional resources for scaffolding their completion of cognitive and communicative activities. Our results suggest that learners set out from an initial stage in which they have little possibilities of participating in communicative activities in the target language, and progressively, through practice, and through the use of interlinguistic (e.g. recourse to resources from other named languages in their plurilingual repertoire) and intralinguistic (lexical substitution and paraphrasing) procedures, they learn to participate in interactions in unilingual mode in that language. We then argue that as plurilingualism is a reality both of social interaction and of learning processes, it should be 'didacticised'; that is, transformed into classroom teaching methodology. We introduce our understanding of the didactics of plurilingualism, an approach based on project-based learning, and discuss its operation on the macro, meso and micro levels.